Relationship Between Schmidt Hammer Rebound Hardness Test and Concrete Strength Tests for Limestone Aggregate Concrete Based on Experimental and Statistical Study - Tunc, Esra Tugrul (Mdpi, 2025)
This study investigated the mechanical properties of concrete specimens produced with a limestone aggregate through laboratory testing. Destructive tests, specifically concrete compressive strength and splitting tensile strength tests, were conducted. Additionally, the Schmidt hammer rebound hardness test, a non-destructive method, was performed on the same specimens. The experimental results, obtained from varying water-to-cement and limestone aggregate-to-cement ratios, yielded the following ranges: compressive strength from 23.6 to 42.6 MPa, splitting tensile strength from 3.2 to 5.1 MPa, and Schmidt hammer rebound values from 18 to 43 N. The correlation between the non-destructive and destructive test results was analyzed experimentally and statistically. Utilizing the experimental data, statistical models were developed, resulting in equations with a high determination coefficient (R2 > 0.95) for accurately predicting concrete compressive and splitting tensile strengths. This approach offers the potential for significant labor and time savings in the production of sustainable conventional concrete that meets relevant standards. Furthermore, it aims to facilitate the estimation of concrete strength in existing structures.
Keywords: concrete strength; Schmidt hammer rebound hardness; destructive testing; non-destructive testing; statistical methods